2008
DOI: 10.1007/s12010-008-8228-x
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Micellar Extraction of β-Galactosidase from Barley (Hordeum vulgare)

Abstract: The reverse micellar system of sodium bis(2-ethylhexyl)sulfosuccinate (AOT)/isooctane was used for the extraction and primary purification of beta-galactosidase (EC 3.2.1.23) from the aqueous extract of barley (Hordeum vulgare) for the first time. The process parameters such as the concentration of the surfactant, the volume of the sample injected, and its protein concentration, pH, and ionic strength of the initial aqueous phase for forward extraction, buffer pH, and salt concentration for back extraction are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several reports on the application of RME for separation and purification of biomolecules are available for model systems (4)(5)(6)(7)(8). In recent years, a few studies on RME of biomolecules from natural=real systems have been reported (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports on the application of RME for separation and purification of biomolecules are available for model systems (4)(5)(6)(7)(8). In recent years, a few studies on RME of biomolecules from natural=real systems have been reported (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…But beyond this concentration, there is a fall in protein transfer to the organic phase. This infers that very less concentration of AOT fails to form sufficient number of reverse micelles in organic phase and higher concentration leads to disruption of reverse micelles which lowers the transfer of protein to organic phase [9] .…”
Section: Effect Of Aot Concentrationmentioning
confidence: 96%
“…The absorbance of onitrophenol formed by the enzyme reaction was measured in alkaline medium at 410 nm using a spectrophotometer (Shimadzu UV-160A, Japan). One unit of β-galactosidase activity was defined as the amount of enzyme that released 1 nmol of o-nitrophenol per minute under standard conditions of 37 o C and pH 4.0 for 15 min [28].…”
Section: Enzyme Assaymentioning
confidence: 99%